The Effectiveness of an Educational Program Based on the Inferential Hypothesis Theory in Creative Writing among Students of the Department of Arabic Language (Journal of the College of Basic Education, 2025)
This study aims to develop an instructional program grounded in the Inferential Hypothesis Theory and to examine its effectiveness in enhancing creative writing skills among students of the Department of Arabic Language at Al-Mustansiriyah University. The researcher adopted a quasi-experimental design (post-test control group) and selected a purposive sample of 151 students, distributed into an experimental group (75 students) taught through the instructional program and a control group (76 students) taught using the conventional method. The groups were statistically equated in several variables, including chronological age, intelligence, linguistic ability, and parental academic achievement.A creative writing test consisting of 20 items was developed, validated, and tested for reliability. Data analysis revealed statistically significant differences at the level of (0.05) in favor of the experimental group in the creative writing test, as well as in the delayed post-test, confirming the effectiveness of the instructional program in developing creative writing skills